ALETHEIA research project: Arts and art therapy as an approach to trauma and emotional memory - Cristina Masini Fernández; Mónica Cury Abril (Arteterapia)
This article presents the ALETHEIA research work that is being carried out at the Psychiatric Day Hospital of Vallecas, Infanta Leonor University Hospital. It focuses on the definition of the methodology used by Art Therapy and Psychodrama in the specific care of Complex Trauma, on patients with severe mental illness treated there. The approach of these artistic therapies is framed in a multi and transdisciplinary work. The theoretical foundations, the objective and the methodological framework of the investigation are here presented, pending the final results by the end of 2019.